1980
DOI: 10.1111/j.1471-0528.1980.tb04489.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Menstrual Blood Loss by Danazol in Unexplained Menorrhagia: Lack of Effect of Placebo

Abstract: Summary In women with menorrhagia of unknown cause, the efficacy of the drug danazol in reducing heavy menstrual blood loss was investigated making objective measurements of menstrual blood loss. Drug regimens tested were daily administration of 200 or 100 mg danazol for 12 weeks and daily danazol given in the luteal phase or during menstruation. The results suggest that 200 mg danazol daily is the most acceptable regimen clinically since it significantly reduced menstrual blood loss and was associated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…A danazol-loaded IUD has been shown to be an effective and conservative treatment for dysmenorrhea, pelvic pain, and dyspareunia associated with endometriosis (14). This is probably due to the elevated uterine/ pelvic efficacy with limited systemic absorption leading to undetectable serum levels (6).…”
Section: Discussionmentioning
confidence: 99%
“…A danazol-loaded IUD has been shown to be an effective and conservative treatment for dysmenorrhea, pelvic pain, and dyspareunia associated with endometriosis (14). This is probably due to the elevated uterine/ pelvic efficacy with limited systemic absorption leading to undetectable serum levels (6).…”
Section: Discussionmentioning
confidence: 99%
“…Ours was an uncontrolled study and there was potential for placebo effect. Most studies are unable to demonstrate such an effect (Chimbira et al 1980b) in the treatment of DUB, but this must be verified by further controlled studies.…”
Section: Discussionmentioning
confidence: 96%
“…It may be that the bleeding was consistent during therapy and not intermittent as in her normal period which meant that she did not flood or pass clots even though the objective menstrual loss was greater. The effect on symptoms compares favourably with danazol (Chimbira et al 1980b) and the prostaglandin synthesis inhibitors (Fraser et al 1981; Mira et al 1986). Ours was an uncontrolled study and there was potential for placebo effect.…”
Section: Discussionmentioning
confidence: 98%
“…It has both antiestrogenic and antiprogestogenic activity. It reduces estrogen levels and thereby causes endometrial atrophy and amenorrhea in some women [31]. In the Cochrane Review by Beaumont et al [14], despite wide confidence intervals, danazol (100 -200 mg daily) was found to be more effective in reducing menstrual blood flow than placebo, progestins, NSAIDs and oral contraceptive pills, but it has more side effects than NSAIDs and progestins.…”
Section: Other Medical Treatmentsmentioning
confidence: 98%